The Influence of Spiritual Leadership on Organizational Citizenship Behavior: Mediation of Emotional Intelligence - Rahmawati, Christina Heti Tri; Purnomo, Hadi -; Purnamarini, Tri Ratna; Kurniawan, Ignatius Soni; Hartono, M Edhie (Business Management Journal, 2023)
Organizational Citizenship Behavior (OCB) is the attitude of an employee who works for a company or organization without asking the company for compensation for what they do. This research aims to determine (1) the influence of spiritual leadership on OCB; (2) the influence of spiritual leadership on emotional intelligence; (3) the influence of emotional intelligence on OCB; and (4) the influence of spiritual leadership on OCB mediated by emotional intelligence in PT. Catur Kencana Management Yogyakarta employees. The population of this study were all employees of PT. Catur Kencana Management Yogyakarta. This research is quantitative research and primary data was taken using a census-taken questionnaire with a sample of 52 respondents. The data analysis technique used in this research is variance-based Structural Equation Modeling (SEM) using the SmartPLS application. The research results show that (1) spiritual leadership influences OCB; (2) spiritual leadership influences emotional intelligence; (3) emotional intelligence influences OCB; and (4) emotional intelligence mediates the influence of spiritual leadership on OCB in PT. Catur Kencana Management Yogyakarta employees. The research results have implications for leaders paying more attention to spiritual leadership, so that it can have a high impact on employee OCB through emotional intelligence.